P270 Clinical characteristics of childhood hydatid disease: a single tertiary centre experience from turkey. (6th June 2017) - Özdemir, Halil; Karbuz, Adem; Kocabaş, Bilge Aldemir; Yahşi, Aysun; Erat, Tuğba; Bingöl-Koloğlu, Meltem; Fitöz, Suat; Tutar, Ercan; Çiftçi, Ergin; Ince, Erdal
Abstract : Background and aims: Hydatid disease is a parasitic infection and it is a major health problem in some areas. We aimed to evaluate the demographic and clinical findings of patients with hydatid disease in our hospital and to compare our results with previous studies. Methods: Between January 2009 and December 2015, patients who were diagnosed as hydatid disease in our hospital, were included retrospectively in this study. Demographic characteristics, clinical findings, laboratory and imaging results, treatment modalities and complications were collected. Results: Twenty-eight patients were involved in our study. Patients often admitted to hospital with chest pain, cough, fever, abdominal pain, nausea and vomiting. The median age of patients' was 134 (55-197) months. Twenty (71.4%) patients were male. The most common physical finding was decreased breath sounds. Most frequently affected organs were liver (71.4%) and lungs (57.1%). In addition cysts were detected atypical locations such as heart (n=2), brain (n=2), spleen (n=2), pancreas (n=1), kidney (n=1) and pelvis (n=1). Medical treatment was given in all patients with hydatid disease. Treatment modalities were as follows: 60.7% (17/28) surgical treatment, 14.3% (4/28) interventional radiologic drainage, 21.4% (6/28) only medical treatment and 3.6% (1/28) interventional radiology drainage and surgery treatment together. Post operative complications were bile leakage, cholangitis, pneumothorax and fistula. No mortality occurred, but recurrence was seen in 1 (3.6%) patient. Conclusions: Hydatid disease is an important problem in our country. In patients with hydatid disease, there might be multiple organ involvement at the same time. Therefore, advanced imaging methods such as abdominal ultrasonography, echocardiography, and brain magnetic resonance should be used for the detection of localised atypical cysts for all patients. Clinical findings and location of the cysts may help deciding the choice of treatment. Long term outcomes are satisfactory with adequate treatment.